Do objections count? Estimating the influence of residents on housing development assessment in Melbourne. Issue 3 (2nd July 2016) - Jean Taylor, Elizabeth; Cook, Nicole; Hurley, Joe
Abstract: This paper explores relationships between community opposition, planning assessments and local political processes. While resident opposition to development proposals is thought to delay housing supply, the nature, extent and pathways of influence have not been quantitatively established. In Victoria the number of third party objections has no direct legal weight, but in practice, development applications involve multiple decision makers. Community expectations that objection numbers "count" may reflect suspicion that refusals are more likely from elected local decision makers. This paper tests for relationships between procedural and political pathways in planning. It uses descriptive statistics and binary logistic regression models based on one year (15 676) of Melbourne residential development assessments. It is found that objection numbers increase significantly with local socio-economic status and that, as applications receive more objections, elected representatives more often intervene. Assessments by elected councilors are significantly more likely to be refused, and have relative odds more than seven times higher of resulting in appeal. The paper argues that local contestation of housing, particularly from better-resourced groups, is highly adaptable to reforms seeking to overcome or rationalise it. Reducing or shifting opportunities for third party opposition may less reduce planning uncertainty, than increase its variation, complexity, and spatial concentration.